2007
DOI: 10.1016/j.jnucmat.2007.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Carbon transport, deposition and fuel accumulation in castellated structures exposed in TEXTOR

Abstract: In order to maintain the thermo-mechanical durability of ITER it is proposed to castellate the interior surface of the first wall and divertor by splitting them into small-size cells [W. Daener et al., Fusion Eng. Des. 61&62 (2002) 61]. A concern is the accumulation of fuel in the gaps of the castellation. In TEXTOR, molybdenum limiters were exposed in the scrape-off layer (SOL) plasma to assess fuel accumulation. The first limiter was exposed under deposition-dominated conditions. Carbon deposits were formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
(13 reference statements)
3
25
1
Order By: Relevance
“…Modeling attempts to simulate the observed deposition pattern using the same assumptions as reported in [15] resulted in partial success only: a rough qualitative agreement between modeling and experimental data was achieved with a carbon atom reflection coefficient of 50%.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling attempts to simulate the observed deposition pattern using the same assumptions as reported in [15] resulted in partial success only: a rough qualitative agreement between modeling and experimental data was achieved with a carbon atom reflection coefficient of 50%.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Runs were made with a simple particle reflection model, as was used in [15] for three particle reflection coefficients R=0, R=0.5 and R=0.9. 30.000 carbon atoms were started from the three source locations shown in the Fig.4b for the two different geometries.…”
Section: Modeling Of Carbon Deposition In the Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier it was noted that simple processes of particle reflection from the gap walls might satisfactorily reproduce experimental deposition patterns [6]. The new findings such as deposition at the bottom of the gaps showed that the modeling algorithms must be improved.…”
Section: Modeling Of the Deposition In The Gapsmentioning
confidence: 97%
“…In DIII-D a heatable sample was exposed to a detached divertor plasma to study the dependence of the gap deposition as function of material temperature. The derived growth rates together with results from the similar experiments in TEXTOR [9,10] can be finally used to obtain an estimate for the growth rate of the ITER in-vessel T-inventory due to deposition inside the gaps of the first wall.…”
Section: Introductionmentioning
confidence: 99%